2009
DOI: 10.1038/msb.2009.27
|View full text |Cite
|
Sign up to set email alerts
|

Targeted tandem affinity purification of PSD‐95 recovers core postsynaptic complexes and schizophrenia susceptibility proteins

Abstract: The molecular complexity of mammalian proteomes demands new methods for mapping the organization of multiprotein complexes. Here, we combine mouse genetics and proteomics to characterize synapse protein complexes and interaction networks. New tandem affinity purification (TAP) tags were fused to the carboxyl terminus of PSD-95 using gene targeting in mice. Homozygous mice showed no detectable abnormalities in PSD-95 expression, subcellular localization or synaptic electrophysiological function. Analysis of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
326
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(345 citation statements)
references
References 66 publications
15
326
1
3
Order By: Relevance
“…The PSD is perhaps the most well-characterized microdomain in the CNS, and several groups have developed cutting edge approaches to interrogate this complex structure in postmortem brain (Cheng et al, 2010;Fernandez et al, 2009;Hahn et al, 2009;MacDonald et al, 2012). Identification and characterization of novel microdomains is currently feasible using standard biochemical techniques.…”
Section: Fluorescence Activated Cell Sorting (Facs) and Single-cell Mmentioning
confidence: 99%
“…The PSD is perhaps the most well-characterized microdomain in the CNS, and several groups have developed cutting edge approaches to interrogate this complex structure in postmortem brain (Cheng et al, 2010;Fernandez et al, 2009;Hahn et al, 2009;MacDonald et al, 2012). Identification and characterization of novel microdomains is currently feasible using standard biochemical techniques.…”
Section: Fluorescence Activated Cell Sorting (Facs) and Single-cell Mmentioning
confidence: 99%
“…Although these studies identified only a small collection of proteins relative to the thousands of proteins now known to occupy the excitatory PSD (Bayes and Grant, 2009), they were among the first to identify additional PSD-associated proteins vital to postsynaptic functioning, including an array of cytoskeletal and scaffolding proteins, cell-adhesion molecules, and proteins modulating small G-protein signaling, adaptor proteins, glutamate receptors, and various signaling molecules (Husi et al, 2000;Walikonis et al, 2000;Satoh et al, 2002). Building upon these early results, more recent investigations have utilized proteomic techniques ranging from SDS-PAGE and 2-DE coupled with mass spectrometry (Jordan et al, 2004;Li et al, 2004;Peng et al, 2004;Collins et al, 2006;Dosemeci et al, 2006;Klemmer et al, 2009), to ICAT labeling or MudPIT (Li et al, 2004;Yoshimura et al, 2004;Phillips et al, 2005;Schrimpf et al, 2005;Moron et al, 2007), and even tandem affinity purification (TAP) tagged-PSD-95 knock-in mice coupled with 1-DE and LC-MS/MS analysis (Fernandez et al, 2009) to identify thousands of proteins that are associated with the structure and function of the excitatory PSD (Collins et al, 2006;Fernandez et al, 2009;summarized in Table 2). Although the importance of these studies in elucidating the molecular and chemical components of the excitatory PSD cannot be overstated, only recently have the powerful tools Figure 1.…”
Section: Neuroproteomics Of the Synapsementioning
confidence: 99%
“…Ces approches ont été utilisées avec succès dans différents cas de cancer et ont confirmé le rôle des kinases/phosphatases et des GTPases au sein des mécanismes d'intégration des voies de signalisation favorisant la tumorigenèse et l'acquisition de potentiel métastatique [19,36]. Ce type d'approche commence à être appliqué aux maladies cognitives et comportementales telles que la schizophrénie, la DI et l'autisme [20,21]. Ces études ont en particulier permis de relier la GAP SynGAP1, qui est associée à des formes non syndromiques de DI (Tableau I), à de nombreux gènes associés à la schizophrénie, suggérant que ces deux sortes de désordres cognitifs résulteraient de perturbations partageant des mécanismes moléculai-res similaires [20].…”
Section: Revuesunclassified
“…Ce type d'approche commence à être appliqué aux maladies cognitives et comportementales telles que la schizophrénie, la DI et l'autisme [20,21]. Ces études ont en particulier permis de relier la GAP SynGAP1, qui est associée à des formes non syndromiques de DI (Tableau I), à de nombreux gènes associés à la schizophrénie, suggérant que ces deux sortes de désordres cognitifs résulteraient de perturbations partageant des mécanismes moléculai-res similaires [20]. Cette hypothèse a été confirmée expérimentale-ment, ce qui conforte la validité du recours à la biologie des systèmes pour mieux comprendre les mécanismes pathologiques associés à des désordres cognitifs et comportementaux [22].…”
Section: Revuesunclassified